(untitled) (Physical Education, Health and Social Sciences, 2026)
Cotton Leaf Curl Disease (CLCuD) represents a catastrophic viral syndrome that perpetually threatens the economic stability of the global textile industry, particularly in the Indo-Pak subcontinent. Transmitted exclusively by the whitefly Bemisia tabaci, specifically the highly competent Asia II 1 cryptic species, the disease is caused by a complex of monopartite begomoviruses and associated DNA satellites. This paper examines the historical genesis of CLCuD, from its 1912 discovery in Nigeria to the current emergence of highly recombinant, resistance-breaking strains like CLCuMuV-Rajasthan in South Asia. We analyze the genomic architecture of the begomovirus-satellite complex, highlighting the critical role of the beta protein in suppressing host immune responses and inducing severe morphological distortions. Furthermore, the review details the molecular mechanisms of circulative persistent transmission, the impact of biometeorological factors such as humidity and temperature on epidemic intensity, and the strategic deployment of advanced biotechnologies like RNAi and CRISPR-Cas12a. The integration of climate-informed AI forecasting and precision vector monitoring is proposed as an essential framework for securing the future of global cotton production.